The Role of Supply Chain Integration in Mediating the Effect of IT Ambidexterity on Supply Chain Resilience in Logistics Service Providers in Indonesia - Sekar Widyastuti Pratiwi; Apsada Juhri; Siska Amonalisa Silalahi; Veronica Veronica; Wahyu Poncotoyo (Jurnal Ilmu Manajemen Terapan, 2026)
Achieving supply chain resilience in the logistics sector demands a nuanced understanding of how digital capabilities translate into operational robustness. This study examines the mediating function of Supply Chain Integration (SCI) in the relationship between IT Ambidexterity (ITA) and Supply Chain Resilience (SCR) within Indonesian logistics service providers. Drawing on survey responses from 91 members of ASPERINDO Jakarta and employing Partial Least Square Structural Equation Modeling (PLS-SEM), the findings reveal that ITA exerts a positive and significant influence on both SCI and SCR. More critically, SCI emerges as a meaningful intermediary through which the resilience-enhancing properties of IT capabilities are channeled to supply chain partners. These results advance the understanding that digital balance — the simultaneous refinement of existing IT assets and pursuit of new technological frontiers - generates the inter-organizational connectivity that fortifies supply chains against disruption. The findings carry practical significance for logistics firms navigating Indonesia’s complex regulatory and infrastructure landscape, suggesting that strategic IT investment should be oriented toward enabling integration rather than mere operational automation.